Effect of exercise intensity on oxygen consumption kinetics in non-exercising muscle during exercise - Nagasawa, Takeshi (Clinical Physiology and Functional Imaging, 2012)
Summary This study examined the effect of exercise intensity on the kinetics of muscle oxygen consumption in non‐exercising forearm flexor muscles () during exercise. Seven healthy male subjects performed cycling exercise for 60 min at 30% of maximal oxygen consumption (%) and 30 min at 50% on separate days. The values at rest and during exercise were measured by near‐infrared spectroscopy. The at 30% significantly increased to 1·2 ± 0·1‐fold over resting value at 20 min after the beginning of exercise (P<0·05) and remained constant within 1·2‐ to 1·3‐fold over resting value until 60 min during exercise. The at 50% significantly increased to 1·2 ± 0·1‐fold over resting value at 15 min after the beginning of exercise (P<0·05). Subsequently, the at 50% increased with time to 1·3 ± 0·1‐fold over resting value at 20 min after the beginning of exercise and to 1·5 ± 0·2‐fold over resting value at 30 min. The 15–30 min of exercise at 50% was significantly higher than that at 30% (P<0·05). These data suggest that the increase in has a time lag from the beginning of exercise, and the kinetics of during exercise differs with exercise intensity. Therefore, we conclude that the kinetics of during exercise is dependent on exercise intensity.